Faculty development and partnership with students to integrate sustainable healthcare into health professions education. (2nd October 2020) - Tun (May Sanyu Tun), SanYuMay; Wellbery, Caroline; Teherani, Arianne
Abstract: There is an urgent need for health professionals to address the impacts of accelerating global environmental change. Healthcare faculty therefore have to educate the rising generation of health professionals in subjects unfamiliar to themselves, such as planetary health and sustainable healthcare. This creates a new paradigm where faculty have to learn a new subject area and incorporate and teach it within their own material. It is important to develop faculty knowledge and confidence to integrate education for sustainable healthcare into their educational practice, as faculty can rapidly acquire and build on these skills. Partnership between students and faculty can enhance this faculty development as students bring fresh ideas and possibly greater knowledge of the climate and ecological crisis. Under supervision, they can co-create the necessary new learning. Students can also act as partners in advocating for social and environmental fairness and systemic change toward a sustainable healthcare system. We summarize the impact of various activities of health professions students around the world which advocate for institutional change and enhance faculty development in education for sustainable healthcare. Through diverse case studies from different countries, we illustrate faculty development in education for sustainable healthcare, highlighting student involvement which has enhanced educators' learning.